The role of the psychologist in achieving the mental health of the school child - Manel Thelaidjia (Social Empowerment Journal, 2019)
Psychological counseling services are a comprehensive psychological education tool that helps to satisfy the needs of our children and strengthen their incentives and enrich their experiences.It contributes significantly to achieve their normal growth according to their inclinations, abilities and preparations, and provides them with guidance to help them solve their academic problems in a scientific and educational manner, and to avoid them feeling of failure This article comes to monitor the reality of the counseling process in the school, and to identify the personal characteristics of the psychologist, which indicate the importance of modern psychological trends and their active role in improving the quality of service. Psychological provided by the school psychologist. Perhaps the most important outcome of directing the attention of educators and those concerned with the preparation and training of psychologists - whether at the university or during the performance of these tasks in schools - the need to search for new alternatives to the programs of preparation and training, or support the current programs with more activities, techniques and capabilities that enable the preparation and training of psychologists, to ensure Have a comprehensive and realistic performance of all psychological services provided in schools